2007
DOI: 10.1055/s-2007-960500
|View full text |Cite
|
Sign up to set email alerts
|

Spannungsoptische Oberflächenanalyse an humanen Femurpräparaten vor und nach Implantation unterschiedlicher Schenkelhalsprothesenmodelle

Abstract: The stress pattern after implantation of the CUT prosthesis remained most similar to the preinterventional stress distribution. Because of this, it is to be expected that the osseous modification would stay at a low level. The question of osteointegration can only be answered in long-term in-vivo studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
2
0
3
Order By: Relevance
“…Auf den Adapter können alle standardmäßig verfügbaren Köpfe aufgesetzt werden [6,18]. Experimentelle Analysen bescheinigen der CUT-Prothese im Vergleich mit anderen Schenkelhalsprothesen eine der physiologischen Situation des proximalen Femurs nahe liegende Lasteinleitung [7][8][9]. Außer kurzfristiger Ergebnismitteilungen existiert lediglich eine Studie, die sich mit den mittelfristigen Ergebnissen der CUT-Prothese befasst (ca.…”
unclassified
“…Auf den Adapter können alle standardmäßig verfügbaren Köpfe aufgesetzt werden [6,18]. Experimentelle Analysen bescheinigen der CUT-Prothese im Vergleich mit anderen Schenkelhalsprothesen eine der physiologischen Situation des proximalen Femurs nahe liegende Lasteinleitung [7][8][9]. Außer kurzfristiger Ergebnismitteilungen existiert lediglich eine Studie, die sich mit den mittelfristigen Ergebnissen der CUT-Prothese befasst (ca.…”
unclassified
“…26 During their biomechanical investigations using the CUT implant amongst other implants Wieners et al found micromotions to be with 165 μm slightly over the critical value of 150 μm. 45…”
Section: Resultsmentioning
confidence: 99%
“…Mit diesem Implantattyp wird eine physiologische proximale Krafteinleitung erzielt und somit ein "stress shielding", wie man es bei diaphysären Verankerungen häufig beobachtet, vermieden [3,6,8,12].…”
Section: Schenkelhalsprothese · Hüftgelenkersatz · Alloarthroplastik unclassified
“…Physiological proximal force induction is achieved with this type of implant with the consequence that "stress shielding" as frequently seen in various methods of diaphyseal anchorage is avoided [3,6,8,12].…”
Section: Schenkelhalsprothese · Hüftgelenkersatz · Alloarthroplastik mentioning
confidence: 99%